2017
DOI: 10.2174/1389203717666160627084304
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Genes Mediating Glucose and Lipid Metabolisms

Abstract: Glucose and lipid are the major energy sources, and pivotal components of organic metabolism in mammals. Inappropriate diet directly influences the metabolic rate, and can alter the body's homeostasis. The underlying changes in energy storage and utilization would manifest as metabolic syndrome including obesity and high blood pressure, and high blood glucose, which are predisposing factors that significantly increase the risk for cardiovascular diseases and Type 2 Diabetes (T2D). Thus, it is essential to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 0 publications
0
13
1
Order By: Relevance
“…The limited increase in the amount of FFAs without enzyme addition at the first 65 min suggested that LF liposomes was not hydrolysed and thus phospholipid membrane could maintain their bilayer structure integrity . However, after addition of pancreatin, most of LF liposomes were degraded, duing to the phospholipids, the main wall materials of liposomes, can be hydrolysed to 1‐acyl and 2‐acyl lysophospholipids and release FFAs . In addition, the main physical function of bile salts is emulsification, attacking liposomes by the mechanism of insertion into the phospholipids, resulting in the membranes more fluid .…”
Section: Resultsmentioning
confidence: 99%
“…The limited increase in the amount of FFAs without enzyme addition at the first 65 min suggested that LF liposomes was not hydrolysed and thus phospholipid membrane could maintain their bilayer structure integrity . However, after addition of pancreatin, most of LF liposomes were degraded, duing to the phospholipids, the main wall materials of liposomes, can be hydrolysed to 1‐acyl and 2‐acyl lysophospholipids and release FFAs . In addition, the main physical function of bile salts is emulsification, attacking liposomes by the mechanism of insertion into the phospholipids, resulting in the membranes more fluid .…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that glycogen is a major source of energy during exercise, and MG content is a determinant of the capacity to perform long‐term heavy exercise . During high‐intensity exercise, MG is exhausted and LG maintains blood glucose in the physiologic range The content of LG and MG has therefore been considered as an important indicator reflecting the level of exercise endurance .…”
Section: Resultsmentioning
confidence: 99%
“…More research would be needed to relate short‐term changes of FA contents at rumen, blood plasma and mammary gland levels, so we are able to distinguish the role of ruminal microbiota and mammary and extramammary tissues . On the other hand, several genes that are involved in the regulation of lipid metabolism and the signalling pathways that regulate expression of those genes have been identified in humans and animals in recent years . However, further studies would allow a better understanding of the regulation of ruminant lipid metabolism at a molecular level …”
Section: Resultsmentioning
confidence: 99%
“…33,34 On the other hand, several genes that are involved in the regulation of lipid metabolism and the signalling pathways that regulate expression of those genes have been identified in humans and animals in recent years. [35][36][37] However, further studies would allow a better understanding of the regulation of ruminant lipid metabolism at a molecular level. 38…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 99%